Why classical music still matters - Kramer, Lawrence, 1946- (Simpson, imprint in humanities, 2007)
In lucid and engaging prose, the book explores the sources of classical music's power in a variety of settings, from concert performance to film and TV, from everyday life to the historical trauma of September 11. Addressed to a wide audience, this book will appeal to aficionados and skeptics alike.